(untitled) (Jurnal Proaksi, 2025)
This study examines whether institutional ownership and foreign ownership influence corporate tax avoidance, with transfer pricing as a mediating variable. Using panel data on 18 palm-oil companies listed on the Indonesia Stock Exchange during 2020–2024 (90 firm-years), we estimate Common, Fixed, and Random Effect models and select specifications via Chow, Hausman, and LM tests; inference relies on robust standard errors. Mediation is evaluated using the Baron–Kenny steps, Sobel test, and a wild cluster bootstrap-t procedure. The results show that institutional ownership has no significant direct effect on tax avoidance and does not significantly affect transfer pricing. Foreign ownership positively and significantly affects transfer pricing, while transfer pricing is negatively associated with tax avoidance. Transfer pricing does not mediate the institutional-ownership–tax-avoidance link; however, under the wild cluster bootstrap-t check, it provides a negative, marginal mediation between foreign ownership and tax avoidance (not confirmed by Baron–Kenny/Sobel). These findings add evidence from an emerging market with diverse ownership and evolving enforcement. They indicate that ownership structure shapes related-party arrangements, whereas stronger transfer-pricing compliance/disclosure aligns with lower tax avoidance. Practically, the results support risk-based oversight and robust documentation of related-party transactions, and they inform investors’ governance/tax-risk assessments and policymakers’ efforts to strengthen compliance frameworks.